Obesity impact on bones and joints health - Mrugała, Waldemar; Skierkowski, Bartosz; Mrugała, Sebastian; Muciek, Michał; Kawka, Jakub; Filipek, Kinga; Czyżewski, Filip; Baranowska, Katarzyna; Baranowska, Alicja; Zalewska, Natalia (Journal of Education, Health and Sport, 2024)
Introduction and objective Obesity, characterized by excessive fat accumulation, poses significant health risks. The WHO classifies overweight as a BMI of 25 to <30 kg/m² and obesity as a BMI of ≥30 kg/m², divided into three classes. This study examines the relationship between obesity and bone health, focusing on osteoarthritis (OA), rheumatoid arthritis (RA), and fracture risks. Review methods A review of epidemiological and clinical studies was conducted, including WHO statistics, U.S. obesity trends, and recent findings on the mechanisms linking obesity with bone health and joint diseases. Studies were selected for their relevance to understanding obesity's impact on skeletal health. Abbreviated description of the state of knowledge Obesity is influenced by sociodemographic, behavioral, and genetic factors. While excess weight was once considered beneficial for bones due to increased mechanical loading, recent research shows its harmful effects. Obesity is linked to chronic inflammation, altered adipokine levels, and higher risk of atypical fractures. In OA, obesity accelerates joint degeneration through mechanical and metabolic pathways. In RA, obesity is associated with increased disease activity and cardiovascular complications. Summary Obesity significantly affects bone and joint health, increasing the risk of OA, RA, and fractures. The paradox of obesity providing mechanical benefits while causing metabolic and inflammatory issues is crucial. Understanding these mechanisms is vital for developing effective prevention and management strategies for obesity-related skeletal diseases. Further research is essential to clarify the complex interactions between adipose tissue and bone health, aiming to improve outcomes for obese individuals.